Studi Karakteristik Hidrolik Saluran Drainase Ruas Jalan A. Yani Km. 29 – Km. 36 Banjarbaru - Ryan Perdana Putra; Maya Amalia (Lambung Mangkurat University Press, 2022)
Banjarbaru is one of the cities in South Kalimantan which has experienced relatively rapid development along with the increase in population and physical buildings. So that it is necessary to improve city services, one of which is revamping the urban drainage network system. Some areas in Banjarbaru are often inundated, and some are even inundated periodically. Hydrological analysis on the evaluation of drainage channels along the A. Yani road Km.29-Km.36 uses the Gumbel distribution method to obtain the design flood discharge. According to the five-year return period calculation, the planned rainfall intensity in one hour is 47.3. From the 5-year return period, the daily rainfall intensity within one hour is 55.8. As for the hydraulics analysis, data were obtained from direct measurements, assumptions based on measurements, and various literatures to be able to calculate channel dimensions. From the results of the identification carried out along the A.Yani Km.29 - Km.36 road, there are 5 points of drainage channels functioning properly and 17 points of drainage channels not functioning properly.